The Sedimentology of the Medina Formation Outcropping Along the Niagara Escarpment (Ontario and New York State) - Martini, Ireneo (My University, 1965)
A field and textural investigation of the Medina Formation has been made. The thesis includes a brief analysis of the microscopic sedimentological properties of the sandy facies, a detailed study of the paleocurrent indicators, and a study of the distribution of the more typical sedimentary structures. Analytical laboratory data, primary sedimentary structures, and outcrop data have been used to reconstruct the paleoenvironmental setting of the Lower Silurian rocks exposed along the Niagara Escarpment from Hamilton (Ontario) to Fulton (New York). They indicate a complex of sub-environments within the broad model of a delta, with the direction of current movement being from the South-East in the eastern part of the area under study and from South-West and North-East in the western part. The determination of these two paleocurrent systems forms a major contribution of this work.
The Sedimentology of the Medina Formation
Keywords: sedimentology; medina formation; niagara escarpment; new york state